"You May Find Yourselves Changed in Unexpected Ways:" Literature and Poverty Law. Issue 3 (2nd September 2017) - Gearey, Adam
Abstract: This paper outlines a tradition of Anglo-American literature that stretches from Jane Addams to Jack London and George Orwell. Locating poverty law scholarship in this tradition of poverty writing has important implications for how we understand lawyering for the poor. Borrowing the idea of unlearning from Addams, this paper argues that reading literature is central to the moral task of self-definition. It may be that poverty lawyering is best understood as a peculiar continuation of a tradition of unlearning that defines the problematic of poverty writing. Orwell's work is central to understanding unlearning. In order to develop these arguments, the latter part of this paper focuses on the work of Lucie E. White. Whilst White's concepts of honesty, self-criticism, and poverty lawyering as "piece work" carry forward elements of unlearning, her engagement with poverty is not pushed far enough. Questions remain about the extent to which understandings of poverty law allow the work on the self to engage with the abjection of being down and out and the politics of socialism that it throws up.